Evaluation of the Circular Economy in a Pitahaya Agri-Food Chain - Diéguez Santana, Karel (2022)
Over the last decade, the circular economy (CE) has attracted attention due to the current unsustainable model of production and consumption, which involves an increased resource use and depletion. Agri-food is one of the key sectors where action must be taken to ensure the transition to a more sustainable development model in line with circular economy principles. This study aims to evaluate the potential of implementing the circular economy in the pitahaya agri-food chain in Ecuador. The research was conducted from 2019 to 2021, during which a checklist was applied that included 91 items grouped into nine dimensions: source or supply of materials, design, manufacturing, economic circle, distribution and sales, consumption/use, 4R, remanufacturing, and sustainability. The level of the circular economy evaluated in the study was low (2.14 points out of 5). Therefore, improvements are required in the agri-food management of fruit cultivation and processing. Critical points were identified and strategies were proposed to increase competitiveness, improve environmental performance, and promote the implementation of the circular economy in this production chain. A final recommendation is to explore research on the concept of CE in the sector, mainly focused on the valorization of biomass as a contribution t